Attitudes of Slovak Consumers towards the Generation of Waste in Tourism - Kubíková, Ľubomíra; Rudý, Stanislav; Kubičková, Viera (Ekonomika, 2025)
The objective of this study is to analyse the relationship between tourist attitudes towards waste generation in Slovakia and their corresponding behaviours. With an increasing emphasis on environmental responsibility, understanding the behaviours and beliefs of tourists concerning waste management is crucial for promoting sustainable practices within tourism. This research focused specifically on tourists visiting Slovakia, offering valuable insights into their waste management attitudes. A questionnaire was distributed electronically to 324 respondents through platforms such as MS Teams, email, and social networks. The questionnaire captured tourist attitudes and behaviours regarding waste generation, responsible consumption, and environmentally sustainable practices. The sample size of 324 responses was validated for representativeness. The statistical method, principal component factor analysis (PCA), was used to assess data suitability and identify the underlying patterns. Correlation analysis was conducted to examine the relationships between variables, with a significance check included. The results showed a significant correlation between tourist attitudes towards waste reduction and their environmentally responsible behaviours. This study provides important implications for promoting sustainable tourism practices in Slovakia and enhancing environmental stewardship in the industry. These findings offer insights that can support more targeted interventions so that to improve waste management in tourism, thereby contributing to Slovakia’s sustainability goals.